2015
DOI: 10.1111/pan.12719
|View full text |Cite
|
Sign up to set email alerts
|

Urethrocutaneous fistula following hypospadias repair: regional anesthesia and other factors

Abstract: In this series, we found no association between the use of caudal regional anesthesia and fistula formation. Location of the starting urethral meatus, prolonged surgical duration, and subcutaneous epinephrine use were associated with fistula formation. Our findings call into question the routine use of epinephrine in hypospadias repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…However, no association between fistula formation and use of caudal anesthesia was noted; instead, this group found that the use of subcutaneous epinephrine was instead associated with an increased risk of urethrocutaneous fistula formation. (12) Because this latter datum was not captured by our surgical database in any consistent or meaningful way, we are unable to comment on whether it may have played a role in our findings (e.g., if subcutaneous epinephrine was used more consistently among patients who also happened to receive caudal anesthesia). Similar to what they report, our surgeon routinely injected lidocaine with epinephrine in the glans during all repairs except the most minimal glanular cases including those with and without caudal anesthetics.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, no association between fistula formation and use of caudal anesthesia was noted; instead, this group found that the use of subcutaneous epinephrine was instead associated with an increased risk of urethrocutaneous fistula formation. (12) Because this latter datum was not captured by our surgical database in any consistent or meaningful way, we are unable to comment on whether it may have played a role in our findings (e.g., if subcutaneous epinephrine was used more consistently among patients who also happened to receive caudal anesthesia). Similar to what they report, our surgeon routinely injected lidocaine with epinephrine in the glans during all repairs except the most minimal glanular cases including those with and without caudal anesthetics.…”
Section: Discussionmentioning
confidence: 93%
“…(9) found complications in 25% of their 342 patients having tubularized incised plate urethroplasty hypospadias repair undergoing a caudal block compared to 15% of those not receiving a caudal block. In contrast, Zaidi et al (12) investigated the incidence of urethrocutaneous fistula formation and its association with caudal anesthesia and found that the location of the urethral opening (proximal > mid > distal shaft) was strongly associated with fistula development. However, no association between fistula formation and use of caudal anesthesia was noted; instead, this group found that the use of subcutaneous epinephrine was instead associated with an increased risk of urethrocutaneous fistula formation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To minimize confounding biases, most studies performed multivariate logistic regression 5 9 10 24. Furthermore, four studies performed subgroup analysis,5 9 10 24 and one study performed matching groups 9. Nevertheless, a higher complication rate appeared in the early time period compared with that of the later period,12 but the trials did not provide relevant information regarding caudal block distributed by time.…”
Section: Resultsmentioning
confidence: 99%
“…However, data were reviewed from institutional billing database and records by trained and independent investigators. The blinding and rigorous reviewing process might decrease selection bias 9. Additionally, surgeries were performed by one surgeon,5 11 23–25 which removes a potential confounding variable of multiple surgeons and potential selection bias 16.…”
Section: Resultsmentioning
confidence: 99%